Comparing the dynamics of biomarkers of neuron-specific enolase and S-100 protein in neonates with hypoxic-ischemic encephalopathy, depending on the start of therapeutic hypothermia (0-6 h vs. 6-24 h after delivery) - D.M. Surkov (Zaslavsky O.Yu., 2019)
Background. To date, it remains unclear whether serum levels of neuron-specific enolase (NSE) and S-100 protein definitely correspond to the severity and possible outcomes of hypoxic-ischemic encephalopathy (HIE), as well as their dynamics during the acute period of HIE, depending on the time when therapeutic hypothermia was started. The purpose was to evaluate the dynamics of such serum biomarkers as NSE and S-100 protein in full-term newborns during the acute period of HIE, depending on the time when therapeutic hypothermia was initiated. Materials and methods. A prospective, single-center cohort study was performed in 205 full-term infants treated in the neonatal intensive care unit (NICU) due to hypoxic-ischemic encephalopathy in 2012-2017. All the babies were stratified by the period from delivery to admission in the NICU. Serum concentrations of NSE and S-100 protein were determined on days 1, 3 and 5 of treatment both in the general cohort and in groups: 0-6 hours (group 1, n = 56) and over 6 hours of life (group 2, n = 149). Results. Dynamics of S-100 significantly changed during 5 days in both groups of newborns (p < 0.001). However, no significant difference was found in the trends of S-100 protein concentration during the first 5 days in both groups (p = 0.082). There was also no statistically significant difference between serum concentrations of S-100 (p = 0.320) in patients admitted in 0-6 hours and later for all five days, except for the first day of admission (p = 0.002). There was no statistically significant difference in NSE level within groups, both in the dynamics from day 1 to day 5 (p = 0.217) and compared to the early (0-6 h) or late (> 6 h) admission to the NICU (p = 0.845). There is also no significant difference in the concentration of NSE among the groups (p = 0.719). Conclusions. No significant differences in the dynamics of S-100 protein and NSE levels in newborns 0-6 hours and over 6 hours after delivery indicated the possibility of initiating therapeutic hypothermia 6 hours after birth, if it wasn't started earlier because of organizing reasons